EXPOSING ENGLISH AS A LINGUA FRANCA TO STUDENTS IN A LISTENING CLASS - Siffa Annisa Fitri Ramadhani, - (2022)
English as a Lingua Franca (ELF) has received more attention in English Language Teaching (ELT) yet its incorporation into ELT classrooms is still less explored. This study aimed to expose ELF to students in a listening class focusing on students' perception toward ELF, contribution of listening activities to students' awareness of English varieties and challenges encountered by students regarding their listening comprehension of English varieties. Employing a mixed-methods explanatory research design, this study was conducted in six meetings of the listening classes in a private university in Jakarta. This study involved 22 students. To collect the data, a questionnaire, listening journals and semi-structured interviews were administered. This study reveals that, first, the students positively perceived ELF in the listening class yet they still expressed strong desire of Standard English (SE) and being native-like speakers. Secondly, listening activities raised students' awareness of English varieties, facilitated students to respect nonnative-accented English in communication and promoted students to accept English varieties in teaching and learning English. Lastly, unfamiliarity with the accents, speakers' speed of speech and lack of vocabulary were the major challenges posed by the students. Therefore, this study offers incorporating ELF along with SE, promoting communicative strategies and involving students to various activities in which they can experience ELF communication as ways to promote students' awareness of ELF. Keyword: English as a Lingua Franca (ELF); Listening; English Language Teaching (ELT) Bahasa Inggris sebagai Lingua Franca (ELF) telah mendapat perhatian lebih dalam pengajaran Bahasa Inggris namun penggabungannya ke dalam kelas masih kurang dieksplorasi. Penelitian ini bertujuan untuk mengekspos ELF ke siswa di kelas mendengarkan yang berfokus pada persepsi siswa terhadap ELF, kontribusi aktivitas mendengarkan terhadap kesadaran siswa tentang ragam bahasa Inggris dan tantangannya. Menggunakan desain penelitian metode campuran eksplanatori, penelitian ini dilakukan dalam enam pertemuan di salah satu universitas swasta di Jakarta. Penelitian ini melibatkan 22 siswa. Untuk mengumpulkan data, kuesioner, jurnal mendengarkan dan wawancara semi terstruktur digunakan. Penelitian ini menemukan bahwa, pertama, siswa mempersepsikan ELF secara positif di kelas mendengarkan namun mereka masih menunjukkan keinginan kuat untuk penutur asli. Kedua, kegiatan mendengarkan meningkatkan kesadaran siswa tentang ragam Bahasa Inggris, memfasilitasi siswa untuk menghormati bahasa Inggris yang tidak beraksen asli dan mendorong siswa untuk menerima ragam bahasa Inggris dalam pengajaran dan pembelajaran bahasa Inggris. Terakhir, aksen yang tidak familiar, kecepatan bicara pembicara dan kurangnya kosakata adalah tantangan utama yang diajukan siswa dalam mendengarkan variasi bahasa Inggris. Oleh karena itu, studi ini menyarankan penggabungan ELF dan SE secara bersamaan, mempromosikan strategi komunikasi dan melibatkan siswa dalam berbagai kegiatan dengan konteks komunikasi ELF. Kata Kunci: Bahasa Inggris sebagai Lingua Franca (ELF); Mendengarkan; Pengajaran Bahasa Inggris (ELT).